2014
DOI: 10.1111/maec.12178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography and population genetic structure of three widespread mollusc species in the Mediterranean and near Atlantic

Abstract: Although several studies have evaluated the genetic structure and phylogeographic patterns in many species of marine invertebrates, a general model that applies to all of them remains elusive. For example, some species present an admixture of populations with high gene flow, whereas others exhibit more complex patterns characterized by small‐scale unstructured genetic heterogeneity, even at a local scale. These differences are thought to be due to clear biological aspects such as direct versus indirect develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 76 publications
(104 reference statements)
2
25
1
Order By: Relevance
“…Evidence of panmixia has been previously provided for other species across some of the regions considered in this study (e. g. mitochondrial marker (D loop): fish species Diplodus sargus , Pagellus bogaraveo , Pagrus pagrus and Scomber japonicus 20 ; mitochondrial markers (Cox1 and 16S): abalone Haliotis tuberculata , chiton Chiton olivaceus 60 ). While we explain the genetic pattern of P .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Evidence of panmixia has been previously provided for other species across some of the regions considered in this study (e. g. mitochondrial marker (D loop): fish species Diplodus sargus , Pagellus bogaraveo , Pagrus pagrus and Scomber japonicus 20 ; mitochondrial markers (Cox1 and 16S): abalone Haliotis tuberculata , chiton Chiton olivaceus 60 ). While we explain the genetic pattern of P .…”
Section: Discussionsupporting
confidence: 56%
“…Despite general evidence of panmixia across several taxa 20 , 60 , rangewide panmixia is extremely rare 9 , 61 . The panmitic genetic pattern described from northern Africa and southern Iberia strongly contrasts with the genetic pattern observed from South African populations of P .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, case studies on galeommatoideans have shown that direct developers can have extensive geographical ranges [29,61] and that indirect developers can be geographically quite restricted [62]. It is known that molluscan species with similar developmental modes can show drastically different population structures [63]. Therefore, the impact of larval ecology on galeommatoidean speciation could be complex and is unlikely to be the major driver of the observed patterns.…”
Section: Discussion (A) Ecological Opportunities For Elevated Diversimentioning
confidence: 99%
“…The particular life cycle of species, and the prevalence of one type of reproduction over the other (sexual vs. asexual), has a great influence on its demography, phylogeography and genetic diversity (Fern andez, Lemer, McIntyre, & Giribet, 2014;Kyle & Boulding, 2000;Sherman, Hunt, & Ayre, 2008;Uthicke, Schaffelke, & Byrne, 2009). As the rate of clonation affects the genetic structure of populations, it also has consequences on their evolutionary potential and their capacity to respond to environmental shifts (de Meeûs et al, 2007).…”
mentioning
confidence: 99%